MEANINGS OF PRIMARY CARE AND FAMILY HEALTH STRATEGY AND THE SINGULARITIES IN ITS DOING - Cristina Condé, Renata; Rosa dos Reis, Roberta; Augusta Silva, Nathally; Corrêa Monteiro, Sylmara; Gonçalves Souto, Rhaissa; Cordeiro Muniz Silva, Elisabete; Souza Fernandes, Patrícia; Leonardo de Oliveira Dias, Cristiano; Gomes Campos Borel, Manuela; Alice de Freitas, Maria; Correia, Andreia; Breno Antunes, Lázaro; et al. (Health and Society, 2023)
Introduction: health, being a sphere of life, in all its diversity, did not remain outside the unfolding of the changes that occurred in society. The Family Health Strategy consists of a strategy for changing the so far existing Brazilian health model experienced until the 1990s. The Family Health Strategy is inserted in a context of political and institutional decision-making to strengthen primary care within the Unified Health System. The multiprofessional health work carried out by the Family Health Strategy (ESF) teams has been characterized by a division of labor among health professionals in order to promote positive and effective impacts on the different factors that interfere in the health-disease process. Objective: to understand the historical trajectory of transformation of the Brazilian health care model with a focus on primary care and its interface with the uniqueness of the performance of professionals working at this level of care. Methods: an integrative literature review study was conducted. Results: the results showed the relevance of the work developed for health effectiveness, in which it is understood that the performance of these professionals should follow a model that integrates competence, knowledge and problem solving. Professionals working in the family health strategy are important in the promotion, information and health education of the communities in which they are included. The work involves a respectful and humanized action with emphasis on autonomy, the development of healthy habits, prevention and health care of the population that meet the new vision of health system in the country. Conclusion: the historical construction of the Brazilian health system has gone through the paradigmatic change of understanding of the health-disease process, requiring dynamic, proactive and community, managerial and interpersonal skills to this reform.